Elucidating the potential of non-edible milkweed seed oil for biodiesel production using green pod-derived nano-catalysts - Kanwal; Okezie Emmanuel; Rozina; Ubani Micheal; Muhammad Zafar (Waste Management Bulletin)
Addressing the dual challenges of greenhouse gas emissions and fossil fuel depletion requires sustainable and cost-effective energy solutions. This study investigates biodiesel production from non-edible Calotropis gigantea L. seed oil using a novel copper oxide (CuO) nano-catalyst synthesized from the green pods of C. gigantea. CuO nanoparticles were characterized using Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), and scanning electron microscopy (SEM). Optimal biodiesel production conditions were achieved at a methanol-to-oil molar ratio of 9:1, reaction temperature of 80 °C, reaction time of 105 min, and catalyst loading of 0.74 wt%, resulting in a 90 % yield. The synthesized biodiesel was characterized through FT-IR spectroscopy, and gas chromatography-mass spectrometry (GC–MS). Physicochemical analysis demonstrated compliance with both European (EN 14214) and American (ASTM D 6751) biodiesel standards, exhibiting favorable properties including density (0.792 kg/L), acid value (0.34 mg KOH/g), kinematic viscosity (6 mm2/s), flash point (91 °C), cloud point (−10 °C), pour point (−8 °C), and minimal sulphur content (0.00097 wt%). These findings establish the viability of converting toxic, non-edible C. gigantea seeds into high-quality biodiesel, presenting a promising pathway toward sustainable energy production while potentially fostering regional socioeconomic development through valorization of agricultural waste.